Implementasi Komputer Vision untuk Mendeteksi Ruang Parkir Kosong pada Kendaraan Roda 4 Berbasis Canny Edge Detection - Harun Al Rasyid; Rachmat Aulia (LKP Unity Academy, 2025)
An automatic parking slot detection system based on image processing offers an innovative solution to overcome parking space limitations and enhance vehicle parking efficiency. This study aims to implement and evaluate the accuracy of a visual-based parking slot detection method. The detection process involves a series of image processing stages, from preprocessing to segmentation of parking slot areas. Based on four tests conducted, the system successfully detected parking slots in all tested scenarios. These results indicate that the implemented algorithm has a high success rate in recognizing empty parking slots. The consistent success across all trials confirms the system's stability and reliability under various visual conditions. These findings provide a strong foundation for further development toward more complex and real-time automated parking systems in real-world environments. Keywords: Parking detection, image processing, empty slot, segmentation, automation.